2010
DOI: 10.1097/qmh.0b013e3181ccbd40
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With the Services of a Pediatric Digestive Tract Endoscopy Unit

Abstract: Global satisfaction is the result of satisfaction with sequential connected caregiving activities administered according to current quality standards. We assessed patients' satisfaction with diagnostic digestive endoscopy via a questionnaire, asking for the state of information, organizational issues, anxiety, pain and discomfort, and medication side effects. A total of 157 patients completed the questionnaire before and after the procedure, and the endoscopy nurse filled it during the procedure. Despite a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Voiosu et al reported that 70.2% of adult patients who underwent colonoscopy considered the information provided prior to the procedure to be insufficient [ 8 ]. Khour et al reported that patient information on medication intake before pediatric digestive endoscopy was insufficient and that patients would appreciate a more detailed description on the type of sedation during the procedure [ 9 ]. In our study, only 30% of both patients and parents replied that they desired a more detailed description of the procedure, which revealed that the participating institutions offered thorough explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Voiosu et al reported that 70.2% of adult patients who underwent colonoscopy considered the information provided prior to the procedure to be insufficient [ 8 ]. Khour et al reported that patient information on medication intake before pediatric digestive endoscopy was insufficient and that patients would appreciate a more detailed description on the type of sedation during the procedure [ 9 ]. In our study, only 30% of both patients and parents replied that they desired a more detailed description of the procedure, which revealed that the participating institutions offered thorough explanations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of patient satisfaction in pediatric endoscopy showed patient understanding of medication intake prior to endoscopy was insufficient and patients would have appreciated a more detailed description of the type of sedation (8). Our study is unique in that we set out to understand the entire patient experience from the patient and family perspective, beyond the patient satisfaction scores previous surveys have traditionally measured.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40] Pediatrics (table 5) We identified six tools used in pediatric anesthesia, which had undergone psychometric development. [41][42][43][44][45][46] Kain et al 44 developed an 11-item questionnaire using a three-step approach starting with validity testing in the form of items grouping using input from anesthetists, surgeons, psychologists, play specialists, and nurses. A rigorous protocol and psychometric evaluation was recently Treatment of discomfort (7), privacy/waiting (10), information giving (7), discomfort (9), treatment pain (4) 6-48 h after returning to ward.…”
Section: Monitored Anesthetic Care (Table 4)mentioning
confidence: 99%
“…Kain et al 44 Yes (1) Yes (1) Content (1) 0.94 (1) NA (0) 68% (1) 5 Khour et al 45 Yes (1) No (0) Content (1) 0.62 (1) NA (0) 100% (1) 4 Tait et al 42 Yes including parents (1) No (0) Content (1) 0.88-0.91 Satisfaction 0.9…”
Section: Maternal Satisfactionmentioning
confidence: 99%